2005
DOI: 10.1021/jo0511039
|View full text |Cite
|
Sign up to set email alerts
|

Opening of Aryl-Substituted Epoxides To Form Quaternary Stereogenic Centers:  Synthesis of (−)-Mesembrine

Abstract: Cycloalkanones are easily converted into aryl-substituted cyclic alkenes by the addition of an aryl Grignard reagent followed by dehydration. These alkenes are good substrates for asymmetric epoxidation. We have found that the addition of allylic and benzylic Grignard reagents can occur preferentially at the benzylic position of the derived epoxides, to give the quaternary stereogenic center. This approach led to a short synthesis of the nanomolar serotonin re-uptake inhibitor (−)-mesembrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Taber and coworkers reported that crude epoxide 74, obtained from the epoxidation of 73 with ketone 42, was regioselectively opened with allylmagnesium chloride to give alcohol 75 in 73% overall yield and 96% ee. Alcohol 75 was subsequently converted into (À)-mesembrine (76) in five steps (Scheme 3.26) [56].…”
Section: ) [24f ] Such Interactions Are Also Supported Bymentioning
confidence: 99%
“…Taber and coworkers reported that crude epoxide 74, obtained from the epoxidation of 73 with ketone 42, was regioselectively opened with allylmagnesium chloride to give alcohol 75 in 73% overall yield and 96% ee. Alcohol 75 was subsequently converted into (À)-mesembrine (76) in five steps (Scheme 3.26) [56].…”
Section: ) [24f ] Such Interactions Are Also Supported Bymentioning
confidence: 99%
“…[1] Notably from a synthetic point of view, the asymmetric creation of the arylic all-carbon quaternary stereocenter in the above cis-aryl hydroindole nucleus constitutes one critical element in the total synthesis of these bioactive alkaloids. [2] Encompassing the asymmetric assembly of the quaternary stereocenters in cisaryl hydroindole alkaloids, various approaches for the direct formation of a carbon-carbon bond centered on the sterically congested chiral quaternary carbon atom have been extensively developed over the past four decades, as mainly exemplified by: 1) 3,3-sigmatropic rearrangement; [3] 2) semipinacol rearrangement; [4] 3) a-alkylation of carbonyls or addition of enolates generated in situ by oxy-Cope rearrangement; [5] 4) Mannich reaction initiated by aza-Cope rearrangement.[6] 5) cycloaddition reaction; [7] 6) Michael addition; [8] 7) epoxide ring opening; [9] 8) intramolecular Heck reaction; [10] 9) intramolecular carbene insertion; [11] 10) intramolecular carbonyl-ene reaction; [12] 11) intramolecular radical cyclization; [13] and 12) intramolecular zirconiummediated diene reductive cyclization. [2] Encompassing the asymmetric assembly of the quaternary stereocenters in cisaryl hydroindole alkaloids, various approaches for the direct formation of a carbon-carbon bond centered on the sterically congested chiral quaternary carbon atom have been extensively developed over the past four decades, as mainly exemplified by: 1) 3,3-sigmatropic rearrangement; [3] 2) semipinacol rearrangement; [4] 3) a-alkylation of carbonyls or addition of enolates generated in situ by oxy-Cope rearrangement; [5] 4) Mannich reaction initiated by aza-Cope rearrangement.…”
mentioning
confidence: 99%
“…[6] 5) cycloaddition reaction; [7] 6) Michael addition; [8] 7) epoxide ring opening; [9] 8) intramolecular Heck reaction; [10] 9) intramolecular carbene insertion; [11] 10) intramolecular carbonyl-ene reaction; [12] 11) intramolecular radical cyclization; [13] and 12) intramolecular zirconiummediated diene reductive cyclization. [14] Among them, however, asymmetric access to the vital quaternary centers was entirely achieved by the diastereoselective induction of the pre-existing stereocenters in chiral substrates or auxiliaries.…”
mentioning
confidence: 99%
See 2 more Smart Citations